Perencanaan kawasan sempadan sungai Yeh Lating untuk pengembangan rekreasi berkelanjutan - Hartadi, I Kadek Dwitya Suma; Utami, Ni Wayan Febriana; Gunadi, I Gusti Alit (Jurnal Arsitektur Lansekap; Vol.5, No.1, April 2019, 2019)
The planning of Yeh Lating riverscape area for sustainable recreation development. Recreation is an activity to fill any free time with non routine activities to get experiences that can bring satisfaction and entertainment. Sustainable recreation planning is a regional planning as place of recreation to meet current needs without compromising the future generations needs.Yeh Lating river in Kerambitan village is one of the potential river in south Kerambitan district, Tabanan regency. This river has been utilized by the surrounding community. However, no special arrangement has been planned as a recreation area, so planning is needed in this area. The method used in this study was field survey with an observation, questionnaires, interviews, and literature study technique. Stages of this study consist of inventory, analysed and synthesis which at the same time become the basic in planning. The results of this study showed that the available potentials in Yeh Lating River including an easy access and also facilities such as dams and beji, while the problems encountered in this study were the border physical problems, cleanliness, structuring, and lack of facilities such as parking. The concept of planning generated in this study was the concept of a combination between Balinese culture with the modern river. Suggestions that can be given was recommendation to the local government of Tabanan in the form of spatial zoning, accessibility, vegetation arrangement, and siteplan planning of Yeh Lating River.